Penerapan Model Pembelajaran Kooperatif Tipe Reciprocal Teaching untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Kelas XI SMA Negeri 14 Medan - Rosalia Rusline Simanjuntak; Saiful Bahri; Cut Latifah Zahari; Evi Julyana Nasution; Safnal Zeryo Sitepu (Journal on Education, 2024)
The aim of this study is to improve students' problem-solving abilities by using the Reciprocal Teaching instructional style. The study included 28 students from class XI IPS 3 at SMA Negeri 14 Medan as participants. The study centred around the subject of Arithmetic Series. First, a preliminary aptitude exam is given, and at the end of each cycle, a problem-solving aptitude test is given. After analysing the first ability test data, it was found that 18 out of 28 students, or 21%, achieved learning completion. The mean score for the test was 26.7. Following the implementation of the Reciprocal Teaching Cooperative learning model, the data analysis findings for cycle I revealed that 13 out of 28 students, equivalent to 61%, achieved learning mastery. The mean score of the class was 70.7. After cycle II, the data analysis showed that 24 out of 28 pupils, or 86%, acquired full learning. The mean score of the class was 90.86. There is an increase in the mathematical problem-solving abilities of students from cycle I to cycle II. Thus, it can be deduced that introducing the Reciprocal Teaching cooperative learning model in class XI IPS 3 at Medan State High School can improve students' aptitude in solving mathematical issues.